Causative Organisms and Risk Factors In Bacterial Meningitis in Al-Elwia Childhood Hospital - Baghdad - Abdul Hameed, Ban (AL-Kindy College Medical Journal, 2011)
Background: Childhood meningitis is a major cause of morbidity and mortality, Hemophilus influenza b (Hib) is the most common cause in many countries, especially below 5 years and before the development of conjugated Hib vaccine, it is followed by Streptococcus Pneumonia, and then N. meningitides, in addition to other microorganisms. Objective: To identify the causative organisms of bacterial meningitis and to identify the factors predisposing significantly to the incidence of bacterial meningitis. Method: This cross sectional , study was done in Al-Elwia Pediatric Hospital during the period 1st of January 2007 to 30th of June 2007.Eighty four patients with presumptive diagnosis of meningitis were included in this study, from the age of 2 months -12 years, History about some risk factors were taken in details. Analysis of cerebrospinal Fluid (CSF) with Gram stains & cultures were done in all cases. Results: The number of cases of meningitis was 50 (20 proved meningitis & 30 partially treated meningitis), while 34 patients are found to have no meningitis. Streptococcus pneumoniae was identified in 45%, Hemophilus Influenza b in 20%, while Nisseria meningitides 5%, other organisms include Escherichia coli, Staphylococcus aureus, Klebsiella, & salmonella. Many factors affecting the occurrence of bacterial meningitis & these include: age, sex, residence, body weight and home overcrowding. Conclusions: Streptococcus pneumoniae was found to be the predominant microorganism causing bacterial meningitis in children aged 2 months-12 years, followed by Hemophilus influenza b, while N. meningitides were one of the rare bacteria which had been identified. E. coli was found to be the major cause in cases of ventriculoperitoneal (VP) shunt meningitis.